Strategies of Increased Protein Intake in ELBW Infants Fed by Human Milk Lead to Long Term Benefits - Mariani, Elisa; Biasini, Augusto; Marvulli, Lucia; Martini, Silvia; Aceti, Arianna; Faldella, Giacomo; Corvaglia, Luigi; Sansavini, Alessandra; Savini, Silvia; Agostini, Francesca; Stella, Marcello; Neri, Erica (Frontiers in Public Health, 2018)
Objective: The aim of this observational study was to evaluate the effects of two different protein intake regimes on feeding tolerance, in-hospital growth, anthropometric data and psychomotor outcome up to 24 months corrected age (CA) in extremely low birth-weight (ELBW; birth weight <1000 g) infants. Methods: During the period 2008-2013, 52 ELBW infants admitted at birth to two Neonatal Intensive Care Units of Emilia Romagna (Italy) were fed according to different protocols of protein fortification of human milk: 26 neonates received a protein intake of 3.5 gr/kg/day (Standard Nutrition Population-SPN) and 26 (Aggressive Nutrition Population-ANP) 4.8 g/kg/day. During hospitalization, infants’ growth, biochemical indices of nutritional status, enteral intake, feeding tolerance, clinical history and morbidity were evaluated. After discharge, anthropometric data and psychomotor outcome, evaluated by Revised Griffiths Mental Development Scales (GMDS-R) 0-2 years, were assessed up to 24 months CA. Results: During hospitalization, the ANP group showed significantly higher weight (18.87 vs. 15.20 gr/kg/day) and head circumference (0.70 vs 0.52 cm/week) growth rates compared to SNP, less days of parenteral nutrition (7.36 ±2.7 vs 37.75 ±29.6) and of hospitalization (60.0±13.3 vs.78.08±21.32). After discharge, ANP infants had a greater head circumference compared to SNP (45.64±0.29; 46.80±0.31). Furthermore, the General Quotient of GMDS-R mean scores in the SNP group significantly decreased from 12 to 24 months CA, while no difference was seen in the ANP group. Conclusions: Increased protein intake may provide short and long term benefits in terms of growth and neurodevelopment in human milk-fed ELBW infants.